Current situation of fisheries in Elazig and neighbouring provinces - Sen, Bulent; Canpolat, Ozgur; Sonmez, Feray (Ege Univ, 2006)
This study is aimed to reveal the current situations of fisheries in Elazig and neighbouring provinces (Malatya, Tunceli, Bingol, Diyarbakir). For this purpose, fish productions obtained from fishing and aquaculture in each province are compared. Natural fish production obtained by means of fishing in Elazig was found to be higher than those in other provinces. The lowest natural fish production belongs to Bingol Province. Mirror carp (Cyprinus carpio) is the most captured fish species in all provinces followed by siraz (Capoetta capoetta umbla). Artificial fish production is currently very low in these provinces. However, taking the amount of artificial fish production into consideration, Malatya takes the first place followed by Elazig. Artificial fish production of rainbow trout (Oncorhynchus mykiss) are below 100 tonnes/ year in Bingol and Tunceli Provinces. In addition. production decreased in these provinces in recent years. Artificial carp production is currently negligible in all these provinces.
Keywords: Aquaculture; Elazig; Malatya; Bingol; Tunceli; Diyarbakir